Tribological behaviour of epoxy based composites for rapid tooling - Pedro V. Vasconcelos (2006)
Epoxy resin composites are frequently applied in moulds manufactured with rapid tooling technologies that are used for wax and polymer materials injection. With the propose of enlarging the application field of the polymer matrix systems, it is fundamental to select adequate dispersed phases and analyse their influence on the composite properties in order to reinforce the polymer matrix and tailor the properties according to the tools specifications. Thermal conductivity and wear resistance are critical parameters for a good service performance and durability of the mould. Metallic fillers allow significant improvement in the resin thermal conductivity. In this work, it was possible to show that small amounts of milled fibres enhance the wear resistance, with little changes in the processability and in the allowed aluminium concentration in the resin matrix. A tribological study of these materials was performed involving the neat resin, the aluminium filled resin and tri-phase composites composed by epoxy, aluminium particles and milled glass or carbon fibres. The study was focused on the role of the particles and fibres in the friction and wear at room temperature and at a typical plastic injection temperature of 160 degrees C. (c) 2005 Elsevier B.V. All rights reserved.